Teaching the Harry Potter Generation - Kerr Houston (Networks: An Online Journal for Teacher Research, 2011)
What I would like to offer here, then, is a brief rumination on some of the ways in which the seven Harry Potter novels and the ensuing eight films may have influenced a number of today’s college students. Clearly, this is hardly a rigorously designed or controlled research project, and it is not a report on a project executed in a classroom. Rather, it is an informal set of reflections on a group of texts that have enjoyed an exceptional popularity among an entire generation of students. Certainly, there should always be a place for focused research into pedagogy and the learning experience. But perhaps there is also room for lighter and more subjective considerations of factors that shape our students’ preconceptions about school – and, as a result, may shape their behavior and our classrooms, as well.